2016
DOI: 10.4103/1735-1995.196618
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and elderly with chronic diseases: A review of the existing literature

Abstract: Background:Increased life expectancy and the growing phenomenon of aging can lead to increased burden of chronic diseases (CDs) which adversely affects the overall health of elderly, their sexuality in particular. Sexual life of an aged population is overlooked in many of the societies. In the present narrative review, we aim to assess the impact of CDs on sexual function of elderly people.Materials and Methods:We used internet databases including PubMed, EMBASE, ISI Web of Science, Google Scholar, SID, Iran M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 76 publications
(91 reference statements)
1
20
0
2
Order By: Relevance
“…It would be useful for healthcare workers to be aware of the multiple ways in which sexual difficulties may be experienced and it’s emotional and relational impact. Healthcare workers should understand that, while aging might bring about changes in sexuality, reduced sexual functioning is by no means an inevitable process of aging [ 12 , 47 ]. To assist healthcare practitioners, more concrete diabetes care guidelines which address sexual dysfunction and well-being, and which are currently limited [ 2 ], need to be developed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It would be useful for healthcare workers to be aware of the multiple ways in which sexual difficulties may be experienced and it’s emotional and relational impact. Healthcare workers should understand that, while aging might bring about changes in sexuality, reduced sexual functioning is by no means an inevitable process of aging [ 12 , 47 ]. To assist healthcare practitioners, more concrete diabetes care guidelines which address sexual dysfunction and well-being, and which are currently limited [ 2 ], need to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in a recent review of global diabetes guidelines, “sexual dysfunction is still an under-appreciated, under-recognized, under-discussed, and commonly untreated complication of diabetes” [ 2 ]. Moreover, little is known about how people with diabetes perceive and experience sexual difficulties, and the bio-psychosocial contexts of these experiences, particularly in low- and middle-income countries (LMICs) [ 10 12 ]. These issues are difficult to identify and explore through checklists of physiologic sexual dysfunction and quality of life scales typically used in quantitative research on sexual functioning [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there was no change in the ASES mean score of the control group, during the last visit compared to the first visit. One of the adverse effects of chronic diseases is that they affect sexual life negatively [ 10 ]. Chronic diseases may damage individuals' sexual functions such as orgasm disorder, ejaculatory incompetence, dyspareunia and suppression of sexual desire and may also cause them to fear sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature's data focus on sexual dysfunctions encountered among men, some evidence shows that respiratory system diseases in women can be accompanied by sexual dysfunction [ 8 ]. A study reported that female COPD patients had less sexual desire and impaired quality of sexual life [ 10 ].…”
Section: Introductionmentioning
confidence: 99%